Interfacial reaction in ASZ/A384 Al composite and its influence on mechanical properties - Lee, JC; Shim, JH; Lee, HI (KOREAN INST METALS MATERIALS, 2003)
In an ASZ/A384 Al composite, the interfacial reaction was observed to take place between the SiO2 binder layer and Mg within the matrix to form MgAl2O4 at the interface. Formation of MgAl2O4 at the interface between ASZ short fibers and the Al matrix alloy is believed to enhance the interfacial bonding strength, resulting in improved composite strength. However, the interfacial reaction in the ASZ/A384 Al proceeds at the expense of Mg in the matrix, resulting in a composite devoid of Mg bearing precipitates such as Al2CuMg and Mg2Si.